• A quadratic function f is given. f(x) = x2 − 4x + 7 (a) Express f in standard form.?

    Best answer: f (x) = [ x^2 - 4x + 4 ] - 4 + 7 f (x) = [ x - 2]^2 + 3
    Best answer: f (x) = [ x^2 - 4x + 4 ] - 4 + 7 f (x) = [ x - 2]^2 + 3
    3 answers · Mathematics · 3 days ago
  • Evaluate ∫ ∛x d x A) 3x^4+ c B) 1/4x^4 C)3/4x^4/3 + c D)3/4x^4 + c PLEASE EXPLAIN ANSWER?

    Best answer: ∫ x^n dx = x^(n + 1) / (n + 1) ∫ x^(1/3) dx = x^(4/3) / (4/3) + c ∫ x^(1/3) dx = (3/4) x^(4/3) + c
    Best answer: ∫ x^n dx = x^(n + 1) / (n + 1) ∫ x^(1/3) dx = x^(4/3) / (4/3) + c ∫ x^(1/3) dx = (3/4) x^(4/3) + c
    4 answers · Mathematics · 1 week ago
  • Maths Problem?

    Best answer: Let work to be done = X units Combined rate = X/7 units/day Rate of work for Albert = X/10 units/day Rate of work for Renzo = X/y units/day X/7 = X/10 + X/y 1/7 = 1/10 + 1/y 1/y = 1/7 - 1/10 1/y = 3/70 y = 70/3 days for Renz0
    Best answer: Let work to be done = X units Combined rate = X/7 units/day Rate of work for Albert = X/10 units/day Rate of work for Renzo = X/y units/day X/7 = X/10 + X/y 1/7 = 1/10 + 1/y 1/y = 1/7 - 1/10 1/y = 3/70 y = 70/3 days for Renz0
    7 answers · Mathematics · 1 year ago
  • In a given amount of time, Jamie drove twice as far as Rhonda. Altogether they drove 90 miles. Find the number of miles driven by each.?

    Best answer: Rhonda drives x miles Jamie drives 2x miles 2x + x = 90 3x = 90 x = 30 Rhonda drives 30 miles Jamie drives 60 miles
    Best answer: Rhonda drives x miles Jamie drives 2x miles 2x + x = 90 3x = 90 x = 30 Rhonda drives 30 miles Jamie drives 60 miles
    4 answers · Mathematics · 2 years ago
  • Can someone explain this to me? if cos(t)=sqrt 2/2 find sin(t+2pi)?

    Best answer: sin t cos 2π + cos t sin 2π sin t + 0 sin t
    Best answer: sin t cos 2π + cos t sin 2π sin t + 0 sin t
    5 answers · Mathematics · 3 months ago
  • Find an equation of the tangent line to the given curve at the given point? 5x^2 + xy + 5y^2 = 11 (1,1)?

    Best answer: 10x + y + x dy/dx + 10y dy/dx = 0 [ x + 10 y ] dy/dx = - y - 10 x dy/dx = [ - 1 - 10 ] / [ 11 ] = - 1 m = - 1 , point (1,1) y - 1 = - 1 ( x - 1 ) y = - x + 2
    Best answer: 10x + y + x dy/dx + 10y dy/dx = 0 [ x + 10 y ] dy/dx = - y - 10 x dy/dx = [ - 1 - 10 ] / [ 11 ] = - 1 m = - 1 , point (1,1) y - 1 = - 1 ( x - 1 ) y = - x + 2
    4 answers · Mathematics · 1 month ago
  • Convert from rectangular to polar coordinates: a.(-9,9) r=9sqrt(2),θ=? b.(-1,sqrt(3)) r=2, θ =?

    Best answer: a) P ( - 9, 9 ) tan Ө = - 1 and Ө is in 2nd quadrant Ө = 3π/4 r = 9 √2 b) tan Ө = - √3 and Ө is in 2nd quadrant Ө = 2π / 3 r = 2
    Best answer: a) P ( - 9, 9 ) tan Ө = - 1 and Ө is in 2nd quadrant Ө = 3π/4 r = 9 √2 b) tan Ө = - √3 and Ө is in 2nd quadrant Ө = 2π / 3 r = 2
    4 answers · Mathematics · 3 months ago
  • Solve the differential equation?

    Best answer: ∫ y² dy = ∫ t dt y³/3 = t²/2 + C
    Best answer: ∫ y² dy = ∫ t dt y³/3 = t²/2 + C
    2 answers · Mathematics · 3 years ago
  • Tangent line to the curve?

    Best answer: f ` (x) = 4x ³ + 2 e^x f ` (0) = 2 = m y - b = m ( x - a ) y - 2 = 2 x y = 2x + 2
    Best answer: f ` (x) = 4x ³ + 2 e^x f ` (0) = 2 = m y - b = m ( x - a ) y - 2 = 2 x y = 2x + 2
    3 answers · Mathematics · 8 months ago
  • Help with math question?

    Best answer: Z = 5 - 5 [ 7Z - 2 ] Z = 5 - 35Z + 10 36Z = 15 Z = 5 / 12
    Best answer: Z = 5 - 5 [ 7Z - 2 ] Z = 5 - 35Z + 10 36Z = 15 Z = 5 / 12
    4 answers · Mathematics · 1 year ago
  • Use mathematical induction to prove that the following statement is true: 10 + 13 + 16 + .. +(3n + 7) = 1/2 n (3n+17). for all n E N?

    Best answer: Let k be any value of n P (k) is proposition that 10 + 13 + 16 ---------+ (3k + 7) = (1/2) k (3k + 17) Have to show this to be true for k = 1 and k = k + 1 Consider k = 1 :- LHS = 10 RHS = (1/2) (1) (20) = 10 thus true for k = 1 Consider k = k + 1 :- to show that 10 + 13 + 16 ------+ (3k + 7) + 3k + 10 = (1/2) (k+ 1) (3k + 20) is... show more
    Best answer: Let k be any value of n P (k) is proposition that 10 + 13 + 16 ---------+ (3k + 7) = (1/2) k (3k + 17) Have to show this to be true for k = 1 and k = k + 1 Consider k = 1 :- LHS = 10 RHS = (1/2) (1) (20) = 10 thus true for k = 1 Consider k = k + 1 :- to show that 10 + 13 + 16 ------+ (3k + 7) + 3k + 10 = (1/2) (k+ 1) (3k + 20) is true Now 10 + 13 + 16 ---------+ (3k + 7) = (1/2) k (3k + 17)__________is true thus , also true is :- 10 + 13 + 16 ----- (3k + 7) + (3k + 10) = (1/2) k (3k + 17) + (3k + 10) 10 + 13 + 16 ----- + (3k + 10) = (3/2) k² + (17/2) k + 3k + 10 10 + 13 + 16 ----- + (3k + 10) = (3/2) k² + (23/2) k + 10 10 + 13 + 16 ----- + (3k + 10) = (1/2) [ 3k² + 23 k + 20 ] 10 + 13 + 16 -----+ (3k + 10) = (1/2) [ k + 1 ] [ 3 k + 20 ] Thus P (k) is true for k = 1 and k = k + 1 Thus true for all k Thus true for k = n thus 10 + 13 + 16 + ------( 3n + 7 ) = (1/2) n (3n + 17)______ for all n Є N
    5 answers · Mathematics · 3 months ago
  • Help me with this equation please?

    Best answer: This is not an equation. An equation requires an = sign. 10000 + 960 [ cos 115⁰ + j sin 115⁰ ] 10000 - 406 + j 870 9594 + j 870
    Best answer: This is not an equation. An equation requires an = sign. 10000 + 960 [ cos 115⁰ + j sin 115⁰ ] 10000 - 406 + j 870 9594 + j 870
    3 answers · Mathematics · 11 months ago
  • How would you solve 10^-x=5^2x?

    Best answer: 2^(-x) 5^(-x) = 5^(2x) 2^(-x) = 5^(3x) (-x) log 2 = (3x) log 5 0 = (3x) log 5 + x log 2 0 = x [ 3 log 5 + log 2 ] x = 0
    Best answer: 2^(-x) 5^(-x) = 5^(2x) 2^(-x) = 5^(3x) (-x) log 2 = (3x) log 5 0 = (3x) log 5 + x log 2 0 = x [ 3 log 5 + log 2 ] x = 0
    5 answers · Mathematics · 3 months ago
  • Maths Higher GCSE Exam style question help!! (Ratios)?

    Best answer: Kiaria_______Jay________Martha x + 7_________x_________2x + 14 x + 7 + x + 2x + 14 = 77 4x = 56 x = 14 Kiaria_______Jay________Martha 21__________14__________42 1_______________________2
    Best answer: Kiaria_______Jay________Martha x + 7_________x_________2x + 14 x + 7 + x + 2x + 14 = 77 4x = 56 x = 14 Kiaria_______Jay________Martha 21__________14__________42 1_______________________2
    9 answers · Mathematics · 3 months ago
  • Hi.I m in Electrical and Computer Engineering School.My iq is 131.Can I finish Eng school earlier than the others?What iq does the average?

    Best answer: In a word , NO. Course must be completed.
    Best answer: In a word , NO. Course must be completed.
    1 answer · Mathematics · 3 months ago
  • Please help with math problem!!! Read description?

    Best answer: x² = x + 6 x² - x - 6 = 0 [ x - 3 ] [ x + 2 ] = 0 x = 3 , x = - 2 y = 9 , y = 4 We agree !!!
    Best answer: x² = x + 6 x² - x - 6 = 0 [ x - 3 ] [ x + 2 ] = 0 x = 3 , x = - 2 y = 9 , y = 4 We agree !!!
    5 answers · Mathematics · 1 year ago
  • How to find the gradient of life when 3y -2x = 6?

    Best answer: 3y = 2x + 6 y = (2/3) x + 2 gradient is 2/3
    Best answer: 3y = 2x + 6 y = (2/3) x + 2 gradient is 2/3
    4 answers · Mathematics · 4 months ago
  • Miscellaneous Quadratic Method to find x, y?

    Best answer: y = 4/x V = π ∫ y² dx_________limits 2 to 3 V = 16 π ∫ ( 1/x )² dx_________limits 2 to 3 V = 16 π ∫ ( x^(-2) dx_________limits 2 to 3 V = - 16 π [ 1/x ]_________limits 2 to 3 V = - 16 π [ 1/3 - 1/2 ] units³ V = - 16 π [ - 1/6 ] units³ V = (8/3) π units³
    Best answer: y = 4/x V = π ∫ y² dx_________limits 2 to 3 V = 16 π ∫ ( 1/x )² dx_________limits 2 to 3 V = 16 π ∫ ( x^(-2) dx_________limits 2 to 3 V = - 16 π [ 1/x ]_________limits 2 to 3 V = - 16 π [ 1/3 - 1/2 ] units³ V = - 16 π [ - 1/6 ] units³ V = (8/3) π units³
    2 answers · Mathematics · 4 months ago
  • Calc/ derivative word prob? The volume of a sphere of radius r is V= (4/3)πr^3 ...?

    Best answer: dV/dt = dV/dr dr/dt dV/dt = 4π r² x 14 dV/dt = 4π (64) x 14 dV/dt = 11264 ins³ / min
    Best answer: dV/dt = dV/dr dr/dt dV/dt = 4π r² x 14 dV/dt = 4π (64) x 14 dV/dt = 11264 ins³ / min
    2 answers · Mathematics · 4 months ago
  • How do i find the answer for log base of 3 1/9=y?

    Best answer: Let log be log to base 3 log [ 1/9 ] = y 3^y = 1/9 y = - 2
    Best answer: Let log be log to base 3 log [ 1/9 ] = y 3^y = 1/9 y = - 2
    3 answers · Mathematics · 2 years ago